'Greatness going off’' in Renaissance Antony and Cleopatra tragedies - Patterson, J (British Academy, 2022)
The suicides of Antony and Cleopatra afforded the Renaissance dramatist various angles on what Shakespeare called ‘Greatness going off’. Renaissance Antony and Cleopatra tragedies in France and England pointedly thematised how the great failed to preserve the dignity of their rank and office in life, and how they fell short of securing personal posthumous renown in death. Antony and his Egyptian queen found themselves unexpectedly upstaged by social inferiors. Renaissance tragedians noted the irony of Antony’s incompetent imitation of his slave, Eros, who took his own life rather than his master’s in a ‘most noble acte’ of disobedience (Mary Sidney Herbert, Countess of Pembroke). Cleopatra’s death, meanwhile, is unceremoniously delayed by a rebel ‘serf’, her treasurer (Etienne Jodelle); it is then facilitated by a garrulous ‘clown’ and a pair of loyal maids, one of whom almost beats the queen out of ‘this vile world’ (Shakespeare). The incongruities are manifest: what is said about Antony’s magnanimity, or Cleopatra’s alluring charms, is noticeably at odds with what is shown of their remorse, clumsiness, even physical debility, as they struggle to prevent their greatness going off. Culturally, Renaissance Antony and Cleopatra tragedies were in tune with the political–religious crises of their day; but they also sounded deeper notes of an aristocracy in slow decline.